1998
DOI: 10.1038/sj.ejcn.1600592
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular skeletal muscle mass: prediction from multiple frequency segmental bioimpedance analysis

Abstract: Objectives: Bioimpedance analysis (BIA) methods have potential to predict appendicular skeletal muscle mass (SM), although available 50 kHz prediction models include, in addition to impedance (Z), an independent age term. An age term in models is undesirable as it re¯ects incomplete understanding of underlying conduction physiology. This study tested the hypothesis, based on¯uid distribution models related to aging, that appendicular SM bioimpedance analysis (BIA) prediction models would no longer include an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 11 publications
6
54
0
Order By: Relevance
“…Body weight is also measured in the leg-to-leg pressure contact BIA; in addition to providing information on fat mass, multifrequency BIA (frequencies up to 300 kHz) may have an added advantage over SF-BIA (50 kHz) for evaluating leg skeletal muscle (25,26). Martinolli et al reported that multi-frequency BIA seems to be a more accurate method than single frequency BIA for estimating the TBW compartment of healthy and obese adults (27).…”
Section: Discussionmentioning
confidence: 99%
“…Body weight is also measured in the leg-to-leg pressure contact BIA; in addition to providing information on fat mass, multifrequency BIA (frequencies up to 300 kHz) may have an added advantage over SF-BIA (50 kHz) for evaluating leg skeletal muscle (25,26). Martinolli et al reported that multi-frequency BIA seems to be a more accurate method than single frequency BIA for estimating the TBW compartment of healthy and obese adults (27).…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation is present between appendicular resistance or impedance and ALST (Pietrobelli et al, 1998a). Adjusting measured resistance/impedance for either limb length or height then allows development of BIA ALST prediction equations.…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity to estimate segmental electrical properties offers the opportunity to estimate appendicular lean soft tissue (ALST), mainly skeletal muscle (Pietrobelli et al, 1998a). A strong correlation is present between appendicular resistance or impedance and ALST (Pietrobelli et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy subjects, segmental BIA has been shown to offer accurate estimates of appendicular body composition (Pietrobelli et al, 1998(Pietrobelli et al, , 2004Malavolti et al, 2003). However, segmental BIA has never been evaluated for the assessment of appendicular muscle mass in PD patients.…”
Section: Introductionmentioning
confidence: 99%